Korkeusgradientin vaikutus piilevien alfadiversiteettiin ja lajien välisiin sukulaissuhteisiin arktis-alpiinisissa vuoristopuroissai - Stigzelius, Tiina (Helsingfors universitet, 2016)
For the conservation of biodiversity, it is important to examine the factors that shape species richness in different ecosystems. Global warming is predicted to be most pronounced in arctic-alpine areas and arctic environments, especially in major ecotones, like environments close to the tree lines. Therefore by examining the species richness, distribution and requirements of species living in mountainous areas, it is possible to assess the effects of climate change in different spatial scales. Elevational gradients are suitable for this kind of research, because many ecosystems processes and structure of local communities change along elevational gradients. Studies carried out in elevational gradients can help us to find out the mechanisms that shape local communities. The elevational patterns of species richness of micro-organisms like diatoms have been studied increasingly lately, but the results of the factors shaping species richness along elevational gradient are varied between different studies and groups of micro-organisms. Therefore it is important to learn more about the factors that shape species richness of micro-organisms along elevational gradients. In this thesis’s the elevational patterns of species richness and species evenness were studied in three different mountain streams in northern Norway and Kilpisjärvi (n= 44). The study also examines the effects of altitude to taxonomic relatedness of diatom species. Diatom and water chemistry samples were collected in August 2013. Generalized linear models (GLM) were used to analyse species richness and the correlation between environmental variables and species richness were examined with pairwise correlation tests. Taxonomic distinctness was calculated with taxondive-command. According to the GLM, the species richness was best explained (49,2 %) by pH of stream water, stream depth, conductivity and altitude. Species evenness was best explained (45,6 %) by water temperature and total nitrogen (TN). Altitude showed a statistically significant relation ...